Finance and inequality: The distributional impacts of bank credit rationing - Choudhary, M. Ali; Jain, Anil (Journal of Financial Intermediation, 2022)
We analyze reductions in bank credit using a natural experiment where unprecedented flooding in Pakistan differentially affected banks that were more exposed to the floods. Using a unique data set that covers the universe of consumer loans in Pakistan and this exogenous shock to bank funding, we find two key results. First, following an increase in their funding costs, banks disproportionately reduce credit to borrowers with little education, little credit history, and seasonal occupations. Second, the credit reduction is not compensated by relatively more lending by less-affected banks. The empirical evidence suggests that a reduction in bank monitoring incentives caused the large relative decreases in lending to these borrowers.